Nonfiction sound and story for film and video : a practical guide for filmmakers and digital content creators - DeLouise, Amy; Ottenritter, Cheryl (Producer's playbook., 2020)
This book guides nonfiction storytellers in the art of creatively and strategically using sound to engage their audience and bring stories to life. Sound is half of film and video storytelling, and yet its importance is often overlooked until a post-production emergency arises. Written by two experienced creators--one a seasoned nonfiction producer/director with a background in music, and one a sound designer who owns a well-regarded mix studio--this book teaches nonfiction producers, filmmakers, and branded content creators how to reimagine their storytelling by improving sound workflow from field to post. In addition to real-world examples from the authors' own experiences, interviews with and examples from industry professionals across many genres of nonfiction production are included throughout. Written in a conversational style, the book pinpoints practical topics and considerations like 360 video and viewer accessibility. As such, it is a vital point of reference for all nonfiction filmmakers, directors, and producers, or anyone wanting to learn how to improve their storytelling. An accompanying Companion Website offers listening exercises, production sound layout diagrams, templates, and other resources.